Replication of Minute Virus of Mice in Murine Cells Is Facilitated by Virally Induced Depletion of p21 - Adeyemi, Richard O. (American Society for Microbiology, 2012)
The DNA damage response to infection with minute virus of mice (MVM) leads to activated p53; however, p21 levels are reduced via a proteasome-mediated mechanism. This loss was sustained, as virus replicated in infected cells held at the G(2)/M border. Addition of the cyclin-dependent kinase (CDK) inhibitor roscovitine after S-phase entry reduced MVM replication, suggesting that CDK activity was critical for continued viral replication and virus-induced reduction of p21 may thus be necessary to prevent inhibition of CDK.